Food quality according to the production system and its relationship with food and nutritional security: a systematic review - Pereira, Nircia; Franceschini, Sylvia; Priore, Silvia (Saúde e Sociedade, 2020)
The guarantee of Food and Nutrition Security (FNS) through the provision of quality food is essential for human development and a protective factor for better health conditions for the population. The aim of this study was to compare the quality of food according to the production system and its relationship with FNS. It is a systematic review of literature, based on the Preferred Reporting Items for Systematic Reviews (Prisma) method, whose data totaled 389 studies, 14 of which were included. Comparative studies between foods produced in conventional and alternative production systems based on ecology have shown beneficial effects of the latter on health since they have superior nutritional quality and are safer for consumption. Regarding the environmental impact, these foods favor sustainable production. On the other hand, the conventional production model showed limitations such as the worldwide contamination of the food chain by pesticide residues and synthetic fertilizers, which can cause damage to health and the environment, leading to food and nutritional insecurity. Information that contributes to the strengthening of sustainable agri-food systems is essential tools for the creation of public policies that act as an intersectoral strategy for the promotion of health and food and nutrition security.